Relationship Among Motor Behavior, Motor Development, and Motor Performance in Children Aged 7–8 Years in China - Zhang, Hongbing; Cheng, Jiajia; Wang, Zongping (Frontiers in Public Health, 2022)
For the children aged 7-8 in China, "immobility" is one of the key problems that hinder their physical and mental development. It’s widely accepted that the development of motor performance in children is accompanied by their physical and mental growth and development. To clearly uncover the relationship among motor behavior, motor development and motor performance, this study conducted an empirical analysis for the children aged 7-8 in China. This study developed the scales for testing the motor performance, motor behavior and motor performance respectively, and then collect data of the three tests from the Children aged 7-8 in China. Canonical correlation analysis was used to analyze the correlation, and partial least squares regression was used to evaluate the relationship between dependent and independent variables. The study found that there was a significant positive correlation between 7- to 8-year-old children’s motor performance, motor behavior and motor development. The three tests are closely related and can be applied to promote children’s sports level through improved training activities for some indicators. The study found that there was no significant difference in the application of the three tests in different age and sex. It lays a foundation for further testing in the high-age group and meets the measurement model requirements of modern medicine’s "The Bio-Psycho-Social Health Promotion Model". The theoretical Motional Quotient model of "The Bio-Behavior-Task" is further constructed to realize the construction of a comprehensive motor performance evaluation system in line with the law of students’ physical and mental development.